Standards of Accounting and Financial Reporting for Voluntary Health and Welfare Organizations (Book). - Henke, Emerson; Zeff, Stephen A. (The Accounting Review, 1965)
Reviews the book "Standards of Accounting and Financial Reporting for Voluntary Health and Welfare Organizations."